Interhemispheric EEG coherence as a candidate biomarker in gambling disorder: evidence of frontal hyperconnectivity and posterior disconnectivity - Yılmazer, Eda; Çinaroğlu, Metin; Ülker, Selami Varol; Tarlacı, Sultan (Frontiers in Neuroscience, 2025)
BackgroundGambling Disorder (GD) is a behavioral addiction marked by impaired decision-making and poor impulse control. We investigated whether resting-state interhemispheric quantitative EEG (qEEG) coherence—a measure of functional connectivity between homologous cortical regions—could serve as a biomarker of GD.MethodsTwenty-nine male patients with GD and 45 healthy male controls underwent resting-state qEEG recording. Coherence was computed for homologous electrode pairs across delta, theta, alpha, and beta bands. Group differences were analyzed using independent-samples t-tests; associations with disorder duration were assessed via age-controlled partial correlations.ResultsConsistent with our hypothesis, GD participants exhibited frontal pole hypercoherence (Fp1–Fp2) across delta, theta, and beta bands, which is likely influenced by prefrontal/orbitofrontal generators. In contrast, GD showed hypocoherence in temporal (T3–T4, T5–T6), central (C3–C4), and parietal (P3–P4) regions across these frequencies. Greater disorder duration was associated with lower beta coherence at F3–F4 and Fp1–Fp2, and higher delta coherence at O1–O2.ConclusionsThese findings reveal a dual pattern of interhemispheric connectivity disruption in GD—hypercoherence at frontal pole sites and hypocoherence in sensorimotor and attentional posterior networks—supporting theoretical models of addiction neurocircuitry. Resting-state qEEG coherence holds promise as a clinically relevant biomarker for GD and may inform the development of neuromodulatory interventions aimed at network rebalancing.